Micro-stories and music from an intermedia perspective: (Brief) study based on the carol "Un camell d'Orient" - Solano Conde, María (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Brief narrative and music provide themselves bidirectionally, as it happens in other artistic disciplines. Consequently, we have micro-stories emerged from musical pieces as well as songs inspired by literary works, or which share some of its characteristics. We are studing this phenomenon considering intermediality, with Manel’s song/micro-story Un camell d'Orient.
Keywords: micro-story; mini-fiction; music; intermediality; Manel; Un camell d'Orient